"We want to live a little longer and our family want[s] us around": A summative content analysis of adherence to COVID‐19‐related guidelines using the Theoretical Domains Framework. Issue 3 (23rd March 2022) - Leather, Jessica Z.; Keyworth, Chris; Epton, Tracy; Goldthorpe, Joanna; Ulph, Fiona; Armitage, Christopher J.
Abstract : Objective: Public adherence to COVID‐19‐related government guidance varied during the initial lockdown in the UK, but the determinants of public adherence to such guidance are unclear. We capture spontaneous reflections on adherence to UK government guidance from a representative UK sample, and use the TDF to identify key determinants of COVID‐related behaviours. Design: The design was cross‐sectional. Methods: Qualitative data were collected from a large sample of UK adults ( N =  2, 252) via an online questionnaire as part of a wider survey about the UK public's responses to the government's COVID‐19‐related guidance. Summative content analysis was used to identify key guideline terms in the data, followed by latent analysis to interpret the underlying meanings behind the terms using the TDF as an analytical framework. Results: Six TDF domains were identified in the data: Environmental Context and Resources; Beliefs about Consequences; Social Influences; Memory, Attention and Decision Processes; Emotion; and Knowledge. Although the samples were motivated and capable of adhering, limitations in their environments, resources, and social support mechanisms restricted behaviour. Self‐reported adherence was sensitive to positive and negative beliefs about the effectiveness of the measures, in addition to interpretations of the terms 'essential' and 'necessary' in the guidance. Conclusions: Despite extensive structural obstacles to adherence, the majority of the British public were able to follow government COVID‐19‐related instructions, provided they had sufficient resources, social support, and positive perceptions about the effectiveness of the measures. Ambiguities surrounding key terminology in the guidance left room for interpretation, which may have contributed to non‐adherence.